(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The present study was conducted to investigate the effect of growth regulator NAA on in vitro shoot proliferation, rooting, and plantlet establishment. Among the different concentrations of NAA, the best increase in shoot weight (0.25 g) and shoot number (8.83) were observed from 0.1 mg/I NAA. The highest shoot length (2.60 cm), number of leaves (4.83), number of roots (5.15), and root length (2.67 cm) were obtained with 0.2 mg/I NAA at 60 DAT. Key Words: Dendrobium orchid, NAA, MS media. DOI: 10.3329/bjar.v34i3.3966 Bangladesh J. Agril. Res. 34(3) : 411-416, September 2009